THE SHEPHERDING NOTION OF AL-IMĀRAH: ABSTRACTING THE AUTHORITATIVE WORLDVIEW OF THE SEMITIC ROOT ʼMR OF PRE-ISLAMIC AND ISLAMIC ARABIA - Abdul Karim, Hafiz; Bakar, Osman; bin Jamil, Khairil Husaini (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2025)
The normative impression of al-imārah often epitomizes this concept as an Islamic invention. Viewed from this particular epistemic standpoint, the authoritative worldview of al-imārah and its Arabic root ʼmr (أمر) invariably symbolizes human-political order, essentially and practically throughout Islamic history. Semantically, however, the root ʼmr in itself seems to offer a greater understanding of its authoritative worldview, particularly in consideration of the fact that it is a common root attested within many Semitic languages, transcending the Arabic semantical field of that root. With a comparative aim, this study seeks to examine the authoritative worldview of al-imārah semantically through its Semitic root ʼmr, attested within two specific temporal frames: the pre-Islamic Arabia period and the Islamic Arabia period. For pre-Islamic Arabia’s attestation of the root, this study utilizes documentary and literary sources, while the Islamic-Arabic lexicon is the main source for the latter period. Attestations of this root in the documentary sources are indicative of two particular worldviews, either solely for the divination context (Ancient South Arabian) or secular-shepherding context (Ancient North Arabian), while the literary sources of Jāhiliyya poetry hinted at an early combination of both contexts. Meanwhile, the Islamic-Arabic lexicon also indicates the same fusion but differs from the literary sources in terms of its Islamic influences and its semantical range, which are more extensive. In many ways, all of them share the essential authoritative-shepherding worldview of guiding and protecting the interests of their respective dominions of either the divine, the secular, or the combination of both.